Unilateral Talon Cusp on Primary Lateral incisor in a three-year-old Libyan Girl: A Case Report and Literature Review. - Elmehdawi, Huda (Libyan Journal of Dentistry, 2017)
Background: Talon cusp is an uncommon dental anomaly; it is a cusp-like projection appears usually on the palatal surfaces of maxillary anterior teeth in both deciduous and permanent teeth. Case report: A threeyear-old Libyan girl seeks the dentist for carious anterior teeth. On examination: asymptomatic talon cusp on the palatal side of tooth 52 was found. Discussion: Talon cusp is more common in permanent dentition than primary dentition, and is relatively rare in primary maxillary lateral Incisor comparing with the primary maxillary central incisors. Conclusion: Talon cusp is asymptomatic, but it could affect esthetic or interfere with occlusion, and might be a sign for a developmental anomaly in its permanent successors, so early diagnosis and management are important.